Interest Rates and Service Quality as Factors Influencing Customers’ Decisions to Choose Time Deposits at Bank Perekonomian Rakyat - Suci Madalena; Samsudin Samsudin; Desi Rubiyanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effects of interest rates and service quality on customers’ decisions to choose time deposits at BPR Monta Baru in Dompu Regency, Indonesia. Research Method: This study employs a quantitative approach grounded in positivist philosophy, with a population of 200 deposit account holders. Using the simple random sampling technique and the Slovin formula, a sample of 67 respondents was selected. Primary data were collected using a questionnaire and subsequently analyzed using multiple linear regression in SPSS. Results and Discussion: The research findings indicate that interest rates and service quality—both individually and jointly—positively and significantly influence customers’ decisions when choosing deposit products. Implications: These findings can serve as a basis for BPR management in formulating strategies to enhance the company’s competitiveness by offering competitive interest rates and improving service quality standards to maintain customer loyalty. Originality: The novelty of this study lies in its integration of Consumer Behavior Theory and the Marketing Mix to examine the factors influencing customer decisions at rural credit banks (BPRs) in regional areas, particularly following the implementation of nomenclature changes under Law No. 4 of 2023.